2011
DOI: 10.19030/tlc.v9i1.6709
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Students Perceptions Of Life In The U.S.

Abstract: Fifty-six students studying at a Chinese college in a southern province were surveyed for this study and asked to describe their experiences if they were to wake up one day to find themselves in the United States as U.S. citizens. A content analysis was performed for the final analysis of the raw data. Chinese students views on the U.S. varied but mainly focused on the positive aspects of life in America. This researcher therefore concluded that Chinese students surveyed through this study did not have realist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Table 1 presents available demographic data for the participants. The current study observed best practices with regard to several ethical considerations, as informed by the British Educational Research Authority (Ozturgut & Murphy, 2009). The study observed informed consent, voluntary participation, the option of withdrawal, confidentiality, proper data maintenance techniques, discretion, and the availability of transcribed interviews for further analysis, upon request of the senior author.…”
Section: Participantsmentioning
confidence: 99%
“…Table 1 presents available demographic data for the participants. The current study observed best practices with regard to several ethical considerations, as informed by the British Educational Research Authority (Ozturgut & Murphy, 2009). The study observed informed consent, voluntary participation, the option of withdrawal, confidentiality, proper data maintenance techniques, discretion, and the availability of transcribed interviews for further analysis, upon request of the senior author.…”
Section: Participantsmentioning
confidence: 99%
“…Therefore, inclusive professionals consider the impact of these systemic factors on an individual’s mental health and well-being to provide effective support (Farrell and Venables, 2009 ). For international students, this means that their experiences in higher education are shaped not only by their academic and personal experiences but also by the social, political, historical and environmental factors that have influenced their lives (Ozturgut and Murphy, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative that mental health services are easily accessible to all students, regardless of their background or needs. Additionally, mental health services should be advertised consistently and clearly across campus, and staff should be trained to identify and respond to the needs of international students (Ozturgut and Murphy, 2009 ). Furthermore, mental health professionals should be available for appointments during convenient hours, and services should be offered at multiple locations throughout the campus.…”
Section: Introductionmentioning
confidence: 99%